Implementasi dan pengaruh prinsip syariah terhadap efektifitas manajemen risiko di lembaga keuangan syariah - afanin, alfenda nafiah (Maliki Interdisciplinary Journal, 2025)
To evaluate the implementation of Sharia principles and their impact on the effectiveness of risk management in Islamic financial institutions. The application of Sharia principles has been shown to significantly enhance risk management effectiveness, particularly in terms of compliance with Sharia regulations and risk management practices that align with Islamic values. The integration of Sharia principles into risk management policies is crucial to support the sustainability and stability of Islamic financial institutions. This study aims to examine the extent to which Sharia principles are implemented in the operations of Islamic financial institutions and their influence on risk management effectiveness. This is expected to strengthen the integrity of Sharia principles within risk management, thereby supporting the overall sustainability and stability of Islamic financial institutions.